Manajemen Pembinaan Atlet Bulutangkis Kota Surakarta (Survei Terkait Persiapan Pekan Olahraga Provinsi Jawa Tengah 2026) - Revina Nuri Wardani; Agus Supriyoko; Danang Adhi Kusuma (MAN Insan Cendekia Jambi, 2025)
The aims of this research are (1) To find out the selection process for badminton athletes in Surakarta City, (2) To find out the training program implemented, (3) To find out the role of coaches, administrators and parents, (4) To find out the facilities and infrastructure, (5) To find out the level of technical, physical and mental readiness, (6) To find out government or sponsor support, (7) To find out the obstacles faced, and (8) To find out the evaluation and follow-up carried out. Data collection was carried out with collect data in study this is observation, interviews, documentation and questionnaires for coaches, management, organizations and athletes. The approach used in study This is a mixed method, namely research that aims for get an overview of something current and current situation​​​ ongoing as well as centered on actual problems.​ Data collection was carried out with collect data in study this is observation, interviews, documentation and questionnaires for coaches, management, organizations and athletes. The study involved 10 subjects, with the collected data analyzed using descriptive statistical techniques presented in the form of percentages and interview results. Based on the results of the analysis of the management of each questionnaire and interview with coaches, management, organizations and athletes, it was obtained that (1) The selection process for badminton athletes for the 2026 Central Java Provincial Games was carried out internally and fell into the